Twin Deficits And Debt In Asean-5 Countries: Panel Data Analysis - Kueh, Jerome; Muhammad Asraf, Abdullah; Yau, Josephine; Audrey, Liwan; Yong, Sze-Wei (2016)
In view of the globalization, current account deficit and fiscal deficit remain the concern among the policy makers. This is due to the importance of the fiscal policy in governing the current account deficit of a country. This study aims to investigate the Twin Deficits phenomenon in ASEAN-5 countries (Indonesia, Malaysia, Philippines, Singapore and Thailand). In addition, the interaction between Twin Deficits and public debt also included in this study to examine the effects of the fiscal policy on current account deficit when considering the different levels of public debt. Panel data analysis is adopted and the sample period covers from 2000-2014 using annually data. Empirical findings indicate that evidence of Twin Deficits can be observed in the ASEAN-5 countries. In terms of the public debt levels, existence of positive association between current account deficits and fiscal deficits only can be observed when the public debt level is considered high.